2018
DOI: 10.1080/17482631.2018.1461514
|View full text |Cite
|
Sign up to set email alerts
|

Former suicidal inpatients’ experiences of treatment and care in psychiatric wards in Norway

Abstract: Purpose: The purpose of this study is to explore how former suicidal inpatients experienced treatment and care in psychiatric wards in Norway following the implementation of the National guidelines for prevention of suicide in mental health care. The focus of the analysis was on aspects of treatment and care with potential for improvement. Method: We interviewed five former inpatients and analysed the data by means of Interpretative Phenomenological Analysis. Results: Experiencing a sense of companionship with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 37 publications
3
49
0
4
Order By: Relevance
“…Medicinske sestre delujejo na različnih področjih, kjer prepoznavajo, posredujejo in vrednotijo stanje Tabela 2: Razporeditev kod po kategorijah Lynch, et al, 2008;Chan, et al, 2009;Meerwijk, et al, 2010;Bregar, 2012;Sakinofsky, 2014;Bolster, et al, 2015;Hagen, et al, 2017;Seixas Santos, et al, 2017;Jansson & Hällgren Graneheim, 2018 Cutcliffe & Stevenson, 2008;Lynch, et al, 2008;Lakeman, 2010;Bregar, 2012;Sun, et al, 2013;Sakinofsky, 2014;Sellin, et al, 2017;Seixas Santos, et al, 2017;Hagen, et al, 2017Hagen, et al, , 2018 Palmieri, et al, 2008;Chan, et al, 2009;Meerwijk, et al, 2010;Bolster, et al, 2015;Lygnugaryte-Griksiene, et al, 2017;Jansson & Hagen, et al, 2018;Hällgren Graneheim, 2018;Wang, et al, 2018 Ukrepi za izboljšanje obravnave in preprečevanje samomora Izobraževanje in usposabljanje na področju samomorilno ogroženih pacientov Povečanje samozavesti medicinskih sester Razvoj preventivnih praks Zagotavljanje podpore medicinskim sestram pri obravnavi samomorilno ogroženih pacientov Izboljšanje načina spopadanja medicinskih sester s samomori pacientov Preprečevanje izgorevanja medicinskih sester Palmieri, et al, 2008;Chan, et al, 2009;Bolster, et al, 2015;Griksiene, et al, 2017;Seixas Santos, et al, 2017;Lygnugaryte-Jansson & Hällgren Graneheim, 2018;…”
Section: Diskusijaunclassified
See 3 more Smart Citations
“…Medicinske sestre delujejo na različnih področjih, kjer prepoznavajo, posredujejo in vrednotijo stanje Tabela 2: Razporeditev kod po kategorijah Lynch, et al, 2008;Chan, et al, 2009;Meerwijk, et al, 2010;Bregar, 2012;Sakinofsky, 2014;Bolster, et al, 2015;Hagen, et al, 2017;Seixas Santos, et al, 2017;Jansson & Hällgren Graneheim, 2018 Cutcliffe & Stevenson, 2008;Lynch, et al, 2008;Lakeman, 2010;Bregar, 2012;Sun, et al, 2013;Sakinofsky, 2014;Sellin, et al, 2017;Seixas Santos, et al, 2017;Hagen, et al, 2017Hagen, et al, , 2018 Palmieri, et al, 2008;Chan, et al, 2009;Meerwijk, et al, 2010;Bolster, et al, 2015;Lygnugaryte-Griksiene, et al, 2017;Jansson & Hagen, et al, 2018;Hällgren Graneheim, 2018;Wang, et al, 2018 Ukrepi za izboljšanje obravnave in preprečevanje samomora Izobraževanje in usposabljanje na področju samomorilno ogroženih pacientov Povečanje samozavesti medicinskih sester Razvoj preventivnih praks Zagotavljanje podpore medicinskim sestram pri obravnavi samomorilno ogroženih pacientov Izboljšanje načina spopadanja medicinskih sester s samomori pacientov Preprečevanje izgorevanja medicinskih sester Palmieri, et al, 2008;Chan, et al, 2009;Bolster, et al, 2015;Griksiene, et al, 2017;Seixas Santos, et al, 2017;Lygnugaryte-Jansson & Hällgren Graneheim, 2018;…”
Section: Diskusijaunclassified
“…Bregar (2012) izpostavlja terapevtski odnos, ki vsebuje neposesivno bližino, empatijo medicinske sestre ter pristnost v odnosu. Pacienti so celo v raziskavi (Hagen, et al, 2018) izrazili, da med hospitalizacijo po poskusu samomora niso mogli zaupati občutkov vsem zaposlenim, ker niso začutili pristne povezave, in močno poudarili pomen pristnega odnosa med medicinsko sestro in pacienti. Kljub temu da morajo imeti medicinske sestre pri svojem delu veliko mero empatije, morajo imeti tudi sposobnost uravnotežiti svoje čustveno izražanje in profesionalno poklicno oddaljenost v odnosu s samomorilnimi pacienti, s čimer pripomorejo k skrbi tako zanje kot zase (Hagen, et al, 2017).…”
Section: Diskusijaunclassified
See 2 more Smart Citations
“…Lately some qualitative research has been published and provided valuable insights into how strict cultural gender norms might contribute to heightened men suicidality (Andoh-Arthur, Knizek, Osafo, & Hjelmeland, 2018;, the importance of spiritual/religious dimension in suicide attempt experience in Ghana (Akotia, Knizek, Kinyada & Hjelmeland, 2014), the process of recovery after a suicide attempt and how formal requirements and lack of direct contact might challenge therapists connection with suicidal patients (Hagen, Hjelmeland, & Knizek, 2018). Hagen at al. (2018a) study revealed that for suicidal patients in psychiatric wards in Norway experiencing a sense of companionship with professionals and receiving individualized care was important.…”
Section: Introductionmentioning
confidence: 99%